(untitled) (Studia austriaca, 2023)
Elfriede Jelinek’s Die Schutzbefohlenen [Charges (The Supplicants)] shows how the fact that those without (acknowledged) rights speak, even though their language is not the language acknowledged by those who are privileged, nonetheless gives them a right to have rights. As a consequence, the privilege is to be doubted, according to which rights would not be universal. This will be explored in the following.